Analysis of High Order Thinking Skill (HOTS) Type Questions in the Final Assessment of Elementary School Theme 2 Class V Academic Year 2021/2022 - Saputro, Uung Gondo; Mahanal, Susriyati; Mashfufah, Aynin (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
The purpose of National Education is to create a prosperous Indonesian society by forming a quality, independent, and able to realize the ideals of the nation. This goal is implied in the field of Education by applying 21st century skills. One form of 21st century literacy that applies higher-order thinking in learning to improve students’ abilities. Application in education is carried out through planning, implementation, and evaluation. The form of evaluation is a test and non-test, one of which is a HOTS-type question to measure high-level thinking ability. The research data is sourced from documents about the final semester assessment of class V theme 2 Malang city for the 2021/2022 school year. The data were analyzed using descriptive and qualitative techniques. The purpose of the study is to determine the application of the end of Semester Assessment class V theme 2 Malang City for the 2021/2022 Academic Year. The results of the study: (1) questions that measure students’ analytical ability emphasize elemental analysis and relationship analysis; (2) questions that measure a student’s synthesizing ability emphasize hypothesizing a symptom; (3) questions that measure students’ evaluation ability emphasize the assessment of a material based on applicable rules; (4) High order thinking skills type questions contain measuring elemental analysis and relationship analysis skills. The commonly used form of the test is multiple choice, while the stimulus uses story illustrations.